Exploration of the flavonoid content of Ziziphus spina-christi leaf extract and antioxidant activity assay through in vitro and in silico methods - Fitrianti Darusman; Taufik Muhammad Fakih; Dwi Syah Fitra Ramadhan; Hilda Aprilia Wisnuwardhani; Teti Sofia Yanti (Universitas Ahmad Dahlan, 2023)
The human body naturally has an antioxidant system to counteract free radical reactivity in a sustainable manner, but if the number of free radicals in the body is excessive, additional antioxidants are needed from food intake, namely vitamin C, vitamin E, carotenes and flavonoids. One plant that has the potential as an antioxidant is Ziziphus spina-christi (ZSC) because it contains phenolics and flavonoids. This study aims to determine the flavonoid content both qualitatively and quantitatively and to test the antioxidant activity of ZSC leaf extract using in vitro and in silico attenuation methods. Determination of the total flavonoid content of ZSC leaf extract using a comparison of quercetin. In vitro the antioxidant activity assay of ZSC leaf extract was carried out by measuring the reducing activity of ZSC leaf extract against the radical DPPH using ascorbic acid as a comparison, while the in silico method used QSAR and pharmacophore modelling techniques. The results showed that the total flavonoid content obtained from ZSC leaf extract was 0.2515 ± 0.0013 mg QE/g D.W with an IC50 of 58.9296 ppm. Furthermore, from the in silico method using pharmacophore modeling and QSAR techniques, 8 hit compounds were obtained from the content of ZSC with IC50 QSAR ranging from 6.57 μM to 0.0004 μM, which was thought to be the metabolite that had the most role in its antioxidant activity. This value indicates that ZSC leaf extract has potential as a very strong antioxidant. ZSC leaf extract can be used as an antioxidant candidate in drug and cosmetic preparations through the oral or percutaneous route. It also proves that QSAR and pharmacophore modelling techniques can be used as confirmatory tests for in vitro results in determining the antioxidant activity of natural materials.